Financial and Institutional Determinants of Cash Holdings in the Oil and Gas Industry - Sergei Gancherka; Wim Westerman (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2018)
At the same time that a dramatic plunge in energy commodities pressured companies in the energy sector to initiate a down-cycle drill by cutting capital expenditures, selling non-core assets, and laying off personnel, the world’s top producers still maintained over half a trillion dollars in liquid assets. The reasons for phenomena such as this in the global oil and gas sector are manifold. The research question for this composition is: What are the determinants, both financial and institutional, which drive oil and gas companies to hold a certain amount of cash on their balances? This paper aims to analyse these determinants in various geographical markets of the European continent over the period of 2010-2014, using models derived from both the ‘tradeoff’ theory and the ‘pecking order’ theory. The empirical results from 800 firms were acquired with panel data regression analyses. They suggest that cash holdings in the sector are negatively affected by the net working capital, leverag, collateral, and firm size, while cash flows and capital expenditures have a positive influence on cash reserves. Besides the financial determinants, we also studied the institutional determinants for the cash levels. Our findings offer evidence that firms in countries with strong governance (as measured by the World Governance Index) hold more liquidity. Furthermore, the state of financial market development (as measured by the Global Financial Centers Index) is also positively related to cash holdings with the consequence that the financial market effect dominates the influence of governance. Our empirical evaluation will be of concern to managers in the oil and gas sector, who should take into consideration the settings of their companies when making corporate cash policy choices.